PERAN STAKEHOLDERS DALAM IMPLEMENTASI KEBIJAKAN PERLINDUNGAN PEREMPUAN DARI TINDAK KEKERASAN DI KOTA SEMARANG - Wati, Mei Sarah; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Women hold the key and are strategic in engraving the next generation, so the protection of women is very important. The Semarang City Government in carrying out safeguards is assisted by various stakeholders, as a form of seriousness, the Government of Semarang City established Regional Regulation No. 5 of 2016 concerning the protection of women and children from acts of violence, this is done to suppress cases of violence. This is a descriptive qualitative research which aims to identify stakeholders as well as to analyze roles and factors that hinder stakeholders in the implementation of women's protection policies in Semarang City. The result of this research shows that the internal stakeholders are the Office of Women’s Empowerment and Child Protection, SERUNI PPT, District PPT, Semarang City PKK which acts as a policy creator, facilitator, implementer and coordinator. Whereas the external stakeholders consists of NGOs, Community Care for Women, related offices, hospitals, academics, security and courts. There are inhibiting factors for the role of stakeholders, namely the low commitment of members who are a part of integrated service center, the lack of available human and financial resources, overlapping tasks and functions of the agency, bureaucratic structures that are prone to victim information leakage, regulations that hinder the handling process, law enforcement processes related to proving difficult cases of violence and the patriarchal culture in the community is still thick. To overcome this problem, the government needs to establish a new regulation related to handling violence, making SOP for women’s protection, increasing cooperation with other parties, outsourcing as well as educating related government offices and the society.